The existence of conventional banking profitability theories in the Islamic banking system - Ahmad, Nor Hayati; Haron, Sudin (Universiti Utara Malaysia, 1998)
This study verifes the existence of profitability theories applied to conventional banks in Islamic banking. With some adjustments to Bourke's methodology, we find that determinants such as capital ratio, liquidity, interest rate and money supply have a similar effect on Islamic banks. There are also differences which could be used as evidence that Islamic banks are, in fact, distinct from conventional banks. Support is found for the risk-aversion theory and no evidence is found for the efficient-structure and expense-preference theories.